Mecanismo de Proteção em SDM-EON Ciente da Prioridade de Tráfego - Lopes, Rafael; Rosário, Denis; Cerqueira, Eduardo; Oliveira, Helder (Anais do Workshop em Desempenho de Sistemas Computacionais e de Comunicação (WPerformance); 2020: Anais do XIX Workshop em Desempenho de Sistemas Computacionais e de ComunicaçãoDO - 10.5753/wperformance.2020.11102, 2020)
With the increase in the number of devices connected to the internet, caused mainly by the rise of the internet of things paradigm, the core of the network tends to suffer from the scarcity of resources, which, in turn, causes a higher rate of connection blocking. This article proposes a algorithm for routing, spectrum and core allocation for spatial-division multiplexing elastic optical networks that uses classes of service with different levels of protection quality to increase the acceptance rate of requests, guaranteeing 100% protection against failures to higher priority flows. The results demonstrate the effectiveness of the proposed algorithm in establishing connections with high priority compared to others found in the literature.